PENERAPAN ETIKA EKOSENTRISME PADA DESA ADAT RAGI HOTANG MEAT DI KABUPATEN TOBA SAMOSIR, SUMATERA UTARA - Saraswati, Titien; Pinem, Feby Astrid br. (Jurnal Arsitektur Komposisi, 2018)
Abstract: Ragi Hotang Meat Traditional Village in Tampahan District, Toba Samosir Regency, North Sumatera Province, already inaugurated as a traditional village by the Ministry of Education and Culture's Director General of Culture on 11 February 2017. In the village there were some traditional houses that had been revitalized, some original traditional houses, ulos woven crafts and the typical sarong of the village, as well as traditional dances. After being inaugurated as a traditional village, the community was asked to do the development of the village themselves as a tourist destination. As an academician, it was a must to contribute to the local government and to the villagers about the development of the village. The question was: how to develop Ragi Hotang Meat Traditional Village into a tourist destination that would not be damaging the nature, but could provide benefits to the nature and its inhabitants? The purpose of this study was to contribute to the local government and villagers on how to develop their village that would not be damaging the nature, but could provide benefits to the nature and its inhabitants. Analysis by examining the data related to Tourism theory and Deep Ecology. Keywords: traditional village, tourism, Deep EcologyAbstrak: Desa Adat Ragi Hotang Meat, di Kecamatan Tampahan, Kabupaten Toba Samosir, Provinsi Sumatera Utara, telah diresmikan sebagai desa adat oleh Dirjen Kebudayaan Kemendikbud pada 11 Februari 2017. Di desa itu terdapat beberapa rumah adat yang telah direvitalisasi, rumah adat asli, kerajinan tenun ulos dan sarung khas desa itu, serta tarian adat. Setelah diresmikan sebagai desa adat, masyarakat diminta untuk melakukan sendiri pengembangan desa itu sebagai destinasi wisata. Sebagai akademisi, dituntut untuk bisa memberikan masukan, baik bagi pemerintah setempat maupun bagi penduduk desa itu. Pertanyaannya: bagaimana Desa Adat Ragi Hotang Meat dikembangkan menjadi destinasi wisata yang tidak merugikan, namun bisa memberikan keuntungan bagi alam dan penduduknya? Tujuan studi ini ialah memberikan masukan kepada pemerintah setempat maupun penduduk desa itu cara mengembangkan desanya agar menjadi destinasi wisata yang tidak merugikan alam maupun penduduknya. Analisis dengan mengeksaminasi data dikaitkan dengan teori Pariwisata dan Deep Ecology.Kata Kunci: desa adat, pariwisata, Deep Ecology